When Online and Offline Environments Meet - Nadine Bol; Tatiana Gromova; Kim Tenfelde; Marjolijn L. Antheunis (University of Zurich, IKMZ - Department of Communication and Media Research, 2024)
Theory of situational privacy and self-disclosure posits that perceived levels of privacy are determined by perceptions of the environment, and that certain levels of privacy are necessary for self-disclosure. In video consultations, auditory and visual aspects of the doctor's environment can cause patients to experience more or less privacy. To provide empirical evidence for these theoretical assumptions, we conducted a 2 (auditory environmental factor: doctor wearing headphones vs. not) by 2 (visual environmental factor: doctor showing the entire office vs. not) between-subjects scenario-based experiment (N = 163). Participants imagined themselves in a video consultation with a doctor and reported their information and territory privacy concerns and willingness to disclose to the doctor. Results showed that the ability to see the doctor's entire office led to lower information privacy concerns, which - in turn - were associated with increased willingness to disclose medical information to a doctor. Wearing headphones by the doctor did not affect privacy concerns and self-disclosure. Manipulations of both the auditory and visual environment were not significantly associated with territory privacy concerns. These results provide direction for further research on environmental factors and their impact on patients' privacy concerns and self-disclosure during medical video communications.